Strategi Pengelolaan SDM Dalam Peningkatan Kinerja Perusahaan Berkelanjutan Di Era Industri 4.0 - Dea putri meliyanti; Ahmad Gunawan (Jurnal Ekonomi dan Bisnis Digital, 2023)
performance in the Industry 4.0 era. This era is characterized by dramatic changes in industry driven by the integration of digital technology into the work environment. The main focus in this article is how organizations can design adaptive and innovative HR management strategies, enabling employees to adapt to rapid technological changes. The research method used is descriptive analysis which prioritizes the decomposition of data obtained through literature studies originating from books, research and recent journals which are then formulated for analysis to form valid research results. The practical implication of HR management strategies in Industry 4.0 is to create a work environment that supports innovation, employee motivation and continuous performance improvement in increasingly complex business competition.